A comparison of performance of high school freshment on the IPAT Culture Fair Test of "g" scale 2 under different conditions - Capitan, Cielo Vicaldo 1940-
This study aimed to find out how modification in the administration of the IPAT Culture Test would affect the performance of Filipino urban and rural high school freshmen. In the test administration, the following conditions were made: (1) instructions in the test manual were followed; (2) no announcement was made as to the timed nature of the test but the time allotment for each test was expanded; and (3) before the test, the subjects were told about the time limits for each test. Results showed that altered conditions of the test administration in the IPAT Culture Fair Test of "g" Scale 2, whether in the form of expanded time limits or announcement as to the timed nature of the test, did not show significant difference in the performances of sub-groups in both rural and high school freshmen.